2020
DOI: 10.1016/j.gore.2020.100645
|View full text |Cite
|
Sign up to set email alerts
|

Uterine cervical cancer associated with obstructed hemivagina and ipsilateral renal agenesis (OHVIRA) syndrome: A case report and review of the literature

Abstract: Highlights Cervical cancer occurring in patients with OHVIRA syndrome is very rare. This case reports on HPV-negative adenocarcinoma located in the nonvisible cervix. Colposcopy and imaging are essential for cervical cancer with uterine malformation. In OHVIRA syndrome, cervical malignancies may be overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The incidence of OHVIRA syndrome remains unknown, with few published case reports thus far. Very few reports are available regarding OHVIRA syndrome with cancer, particularly uterine cervical cancer [ 11 ]. Kaba et al also reported a case of cervical endometrioid adenocarcinoma diagnosed with OHVIRA syndrome [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of OHVIRA syndrome remains unknown, with few published case reports thus far. Very few reports are available regarding OHVIRA syndrome with cancer, particularly uterine cervical cancer [ 11 ]. Kaba et al also reported a case of cervical endometrioid adenocarcinoma diagnosed with OHVIRA syndrome [ 12 ].…”
Section: Discussionmentioning
confidence: 99%